Advances in Microtechnology for Improved Cytotoxicity Assessment - Garcia-Hernando, Maite; Benito-Lopez, Fernando; Basabe-Desmonts, Lourdes (Frontiers in Materials, 2020)
In vitro cytotoxicity testing is essential in the pharmaceutical and environmental industry to study the effects of potential harmful compounds for human health. Classical assays present several disadvantages: they are commonly based on live-death labelling, are highly time consuming and/or require skilled personnel to be performed. The current trend is to reduce the number of required cells and the time during the analysis, while increasing the screening capability and the accuracy and sensitivity of the assays, aiming single cell resolution. Microfabrication and surface engineering are enabling novel approaches for cytotoxicity assessment, offering high sensitivity and the possibility of automation in order to minimise user intervention. This review aims to overview the different microtechnology approaches available in this field, focusing on the novel developments for high-throughput, dynamic and real time screening of cytotoxic compounds.